265Global diabetes trends and associated socioeconomic, lifestyle and health indicators from 1990 to 2017. (2nd September 2021) - Shirai, Yoshiro; Imai, Tomoko; Sezaki, Ayako; Miyamoto, Keiko; Kawase, Fumiya; Abe, Chisato; Inden, Ayaka; Kato, Takumi; Sanada, Masae; Shimokata, Hiroshi
Abstract: Background: This longitudinal ecological study was conducted to determine the global trends in the age-standardised prevalence of type 2 diabetes mellitus (T2DM) and its association with socioeconomic, lifestyle and health indicators. Methods: Data pertaining to the age-standardised prevalence of T2DM (rates per 100, 000) and socioeconomic, lifestyle and health indicators were obtained from several international databases. Data available from 1990 to 2017 for 139 countries with populations of 1 million or greater were analysed, followed by estimation of slopes for T2DM prevalence in each country. The longitudinal association between T2DM and the standardised variables of socioeconomic, lifestyle and health indicators was fitted using a generalised linear mixed-effects model with random intercept for each country and random slope for year. Results: The country-specific age-standardised prevalence of T2DM decreased significantly in 9 countries, remained unchanged in 11 countries and increased significantly in 119 countries. The estimated standardised effect of age-standardised education for T2DM was the largest at − 524.5 (SE; 109.9), followed by − 514.8 (SE; 95.6) for physical activity and 398.8 (SE; 45.8) for body mass index (BMI) (P < 0.0001 for all). Conclusions: The factors strongly associated with global T2DM prevalence and trends were years of education, followed by physical activity and BMI. This study also provides a basis for investigating public health approaches to control the increase in global T2DM prevalence. Key messages: The promotion of policies that reduce international educational disparities may have the potential to reduce the global increase in the number of patients with T2DM.